2015
DOI: 10.3109/10428194.2015.1101098
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase-associated toxicity in children with acute lymphoblastic leukemia

Abstract: Asparaginase is an integral component of multiagent chemotherapy regimens for the treatment of children with acute lymphoblastic leukemia. Positive outcomes are seen in patients who are able to complete their entire prescribed course of asparaginase therapy. Toxicities associated with asparaginase use include hypersensitivity (clinical and subclinical), pancreatitis, thrombosis, encephalopathy, and liver dysfunction. Depending on the nature and severity of the toxicity, asparaginase therapy may be altered or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
174
3
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(204 citation statements)
references
References 108 publications
7
174
3
20
Order By: Relevance
“…In this study, 8.7% of patients exposed to L-asparaginase had documented clinical hypersensitivity reactions, which is consistent with reported incidence rates with native E. coli L-asparaginase (0%-45%) or PEG-L-asparaginase (3%-24%). 27 This relative low incidence could be explained in part by the concomitant use of steroids because immune-suppressive therapy decreases the risk of hypersensitivity reactions by a reduction of high titer antibodies. 28,29 Detection of antibodies was not performed in this study, but it has been previously reported that silent inactivation occurs in 8% to 29% of patients with ALL receiving L-asparaginase.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 8.7% of patients exposed to L-asparaginase had documented clinical hypersensitivity reactions, which is consistent with reported incidence rates with native E. coli L-asparaginase (0%-45%) or PEG-L-asparaginase (3%-24%). 27 This relative low incidence could be explained in part by the concomitant use of steroids because immune-suppressive therapy decreases the risk of hypersensitivity reactions by a reduction of high titer antibodies. 28,29 Detection of antibodies was not performed in this study, but it has been previously reported that silent inactivation occurs in 8% to 29% of patients with ALL receiving L-asparaginase.…”
Section: Discussionmentioning
confidence: 99%
“…While different forms of the drug offer multiple options for patients who experience allergic reactions, all forms are associated with metabolic complications that are difficult to predict, yet intensify with age (1,2,13,16,22,28,31,50,52,62).…”
mentioning
confidence: 99%
“…However, the results of clinical trials, in which prednisone and dexamethasone were administered simultaneously with 6-mercaptopurine and methotrexate, suggest hepatotoxicity and increased activity of liver enzymes, most likely as a consequence of the application of cytostatics [12]. Th e increase in activity of ALT, AST and GGT obtained in this study, are not typical side effects of antineoplastic drugs used according to the protocol [18][19][20][21], but could be explained as result of their concomitant application and interaction with prednisone and dexamethasone, as published in another studies [22,23]. Information in the literature suggest that glucocorticoids may cause disorders of the values of urea and uric acid [9].…”
Section: Discussionmentioning
confidence: 71%